High flow conditions increase Connexin43 expression in a rat arteriovenous and angioinductive loop model - Schmidt, Volker-Jürgen; Hilgert, Johannes G.; Covi, Jennifer M.; Weis, Christian; Wietbrock, Johanna O.; Wit, Cor de; Horch, Raymund; Kneser, Ulrich (PLOS ONE, 2013)
Gap junctions are involved in vascular growth and their expression pattern is modulated in response to hemodynamic conditions. They are clusters of intercellular channels formed by connexins (Cx) of which four subtypes are expressed in the cardiovascular system, namely Cx37, Cx40, Cx43 and Cx45. We hypothesize that high flow conditions affect vascular expression of Cx in vivo. To test this hypothesis, flow hemodynamics and subsequent changes in vascular expression of Cx were studied in an angioinductive rat arteriovenous (AV) loop model. Fifteen days after interposition of a femoral vein graft between femoral artery and vein encased in a fibrin-filled chamber strong neovascularization was evident that emerged predominantly from the graft. Blood flow through the grafted vessel was enhanced ∼4.5-fold accompanied by increased pulsatility exceeding arterial levels. Whereas Cx43 protein expression in the femoral vein is negligible at physiologic flow conditions as judged by immunostaining its expression was enhanced in the endothelium of the venous graft exposed to these hemodynamic changes for 5 days. This was most likely due to enhanced transcription since Cx43 mRNA increased likewise, whereas Cx37 mRNA expression remained unaffected and Cx40 mRNA was reduced. Although enhanced Cx43 expression in regions of high flow in vivo has already been demonstrated, the arteriovenous graft used in the present study provides a reliable model to verify an association between Cx43 expression and high flow conditions in vivo that was selective for this Cx. We conclude that enhancement of blood flow and its oscillation possibly associated with the transition from laminar to more turbulent flow induces Cx43 expression in a vein serving as an AV loop. It is tempting to speculate that this upregulation is involved in the vessel formation occuring in this model as Cx43 was suggested to be involved in angiogenesis.